Unveiling transportation disparities: investigating accessibility gaps in metropolitan cities using GIS—a case study of Alexandria, Egypt - ElDeeb, Sally; Abd EL-Baky, Rowan Adel; Masoumi, Houshmand (Frontiers in Sustainable Cities, 2024)
Public transportation is essential to reduce pollution and traffic congestion in urban areas. However, in densely populated regions like Alexandria, characterized by high population density and limited road infrastructure, accessibility to diverse transportation options is crucial. This study investigates the accessibility of public transportation modes, including railways and buses, and their interaction with informal transit. Questioning if public transportation alone will be sufficient for pedestrians or if the presence of informal transit is crucial, and whether all residents of Alexandria have their rightful accessibility for different transport modes, the goal was to establish an efficient and interconnected transportation network. A survey was conducted in cooperation with Transport for Cairo to investigate all transport routes throughout Alexandria, further using ArcGIS Pro to identify gaps in public transportation coverage. Findings revealed that public transportation alone is insufficient due to limited bus and railway coverage because of their fixed linear routes. Informal transit, like microbuses, plays a vital role in filling these gaps. The study emphasizes the need for a comprehensive and sustainable transportation network that considers both formal and informal transit. These insights can guide policymakers and urban planners in improving public transportation in Alexandria and similar cities worldwide.